2022
DOI: 10.3390/jcm11102770
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Multi-Drug Resistant Organisms’ Gastrointestinal Colonization in an Internal Medicine Ward: The Pandora’s Box

Abstract: Background: Multi-drug resistant organisms (MDRO) are an emerging health problem with an important impact on clinical outcome in Intensive Care Units (ICUs) and immunocompromised patients. Conversely, the role of MDRO colonization in Internal Medicine is less clear. The objective of our study is to evaluate the clinical impact (namely sepsis development, in-hospital and 30-days mortality, and re-hospitalization) of MDRO colonization in Internal Medicine. Methods: Patients admitted to our Internal Medicine Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The GI microbiome plays a key role in colonization resistance against AMR pathogens and Clostridioides difficile [ 7 ]. Numerous epidemiologic studies have demonstrated that GI colonization and pathogen domination frequently precede infection with AMR pathogens [ 8 ], such as vancomycin-resistant enterococcal bacteria in adults undergoing allogeneic hematopoietic stem cell transplantation [ 9 ]. The major risk factor for colonization is receipt of antimicrobials, which disrupt the GI microbiome and lead to low microbial diversity and loss of colonization resistance [ 10 , 11 ].…”
mentioning
confidence: 99%
“…The GI microbiome plays a key role in colonization resistance against AMR pathogens and Clostridioides difficile [ 7 ]. Numerous epidemiologic studies have demonstrated that GI colonization and pathogen domination frequently precede infection with AMR pathogens [ 8 ], such as vancomycin-resistant enterococcal bacteria in adults undergoing allogeneic hematopoietic stem cell transplantation [ 9 ]. The major risk factor for colonization is receipt of antimicrobials, which disrupt the GI microbiome and lead to low microbial diversity and loss of colonization resistance [ 10 , 11 ].…”
mentioning
confidence: 99%